A Trnsys Simulation of a Solar-Driven Air Refrigerating System for a Low-Temperature Room of an Agro-Industry site in the Southern part of Italy. (September 2017) - Cascetta, Furio; Di Lorenzo, Roberto; Nardini, Sergio; Cirillo, Luca
Abstract: Solar cooling technologies are of great interest because the cooling load in buildings is directly correlated to the intensity of solar radiation. In this paper, a feasibility study of a solar cooling system for a cold room in the Southern part of Italy is carried out. This feasibility study can be an example for future achievements in Southern of Italy. The cold room is part of an agro-industrial structure; the set point of temperature is 10°C. The room is 11.0 m long, 9.5 m wide and 3.5 m high. Two sliding doors 3.0 m high are present and strawberries are inside mainly. Thermal loads are evaluated by means of the software TRNSYS 17. Parabolic Though Collectors (PTCs) are employed to capture the solar energy. The solar field extends for 210 m 2 . Two double-effect chillers (with a total installed power equal to 150 kW) for the collectors are employed. In addition, a conventional heat pump is installed to meet the demand for refrigeration during unfavorable weather conditions or during the maintenance of chillers. There are two different storage tanks: a tank with volume 10 m 3 for hot water storage and a tank with volume 40 m 3 for cold storage. The terminal part is constituted by dry coolers. Results are given in terms of heat transfer rates and solar fraction. Besides, an economic analysis is carried out to evaluate the payback time.